APLIKASI TARTEEL SEBAGAI MEDIA BELAJAR UNTUK MENGATASI KESULITAN SISWA DALAM MEMBACA AL-QUR’AN - Moch. Ilyas Hamdani; Moch. Bahak Udin ByArifin (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This study is based on the phenomenon of many vocational high school students struggling to read the Qur'an due to their limited understanding of proper Qur'anic pronunciation. This issue arises because the teaching methods used are less acceptable to the students. The study aims to improve the understanding and pronunciation skills of the Qur'an among 10th-grade students at SMK Telkom Sidoarjo through the implementation of the Tarteel method. The research employs a quasi-experimental design using pretest and posttest, involving 33 students as participants. The results indicate a significant improvement between the pretest and posttest scores, with the highest posttest score reaching 90. Based on statistical analysis, the tvalue (-8.144) > ttable (1.69839), indicating that the application of Tarteel has a positive impact on Qur'anic reading skills. These findings recommend the use of technology in religious education to enhance the quality of Qur'anic teaching and provide insights into the potential of technology in addressing challenges in Islamic education in Indonesia.